Designing a model of antecedents of entrepreneurial orientation and behaviour (case study: administrative agencies in Kerman Province). (11th May 2022) - Mirkamandar, Sima; Beheshtifar, Malikeh; Pourkiani, Masoud; Sheikhy, Ayob
This present study aims to design a model of antecedents of entrepreneurial orientation and behaviour in the administrative agencies in Kerman Province, Iran. Accordingly, first, antecedents of entrepreneurship were identified through exploratory studies and a survey of those experts in the topic using the Delphi technique, and then, identified antecedents were presented in a model and tested in the target statistical population. In the present study, a model of antecedents of entrepreneurial orientation and behaviour was presented. In the model, three sets of independent variables, including organisational (eight variables), individual (four variables) and environmental factors (six variables), were considered. They are of factors directly affecting entrepreneurial orientation and behaviour. Then, based on this model and the data obtained from the questionnaire, the relationship between the antecedents of entrepreneurship and the entrepreneurial behaviour and orientation were investigated using the structural equation modelling approach. The results show that there is a relationship between antecedents of entrepreneurship and entrepreneurial orientation and behaviour in the administrative agencies in Kerman province. Moreover, there is a relationship between organisational, individual and environmental factors and entrepreneurial orientation and behaviour.